PA-X is an avian virulence factor in H9N2 avian influenza virus. (5th March 2021) - Clements, Anabel L.; Peacock, Thomas P.; Sealy, Joshua E.; Lee, Hui Min; Hussain, Saira; Sadeyen, Jean-Remy; Shelton, Holly; Digard, Paul; Iqbal, Munir
Abstract : Influenza A viruses encode several accessory proteins that have host- and strain-specific effects on virulence and replication. The accessory protein PA-X is expressed due to a ribosomal frameshift during translation of the PA gene. Depending on the particular combination of virus strain and host species, PA-X has been described as either acting to reduce or increase virulence and/or virus replication. In this study, we set out to investigate the role PA-X plays in H9N2 avian influenza viruses, focusing on the natural avian host, chickens. We found that the G1 lineage A/chicken/Pakistan/UDL-01/2008 (H9N2) PA-X induced robust host shutoff in both mammalian and avian cells and increased virus replication in mammalian, but not avian cells. We further showed that PA-X affected embryonic lethality in ovo and led to more rapid viral shedding and widespread organ dissemination in vivo in chickens. Overall, we conclude PA-X may act as a virulence factor for H9N2 viruses in chickens, allowing faster replication and wider organ tropism.